Agentes de doenças transmitidas por vetores em cães e gatos domésticos - Gonçalves, Jênifer Malheiros (2015)
This study reports the occurrence of vector-borne diseases (VBD) agents Rangelia vitalii, Babesia vogeli, Hepatozoon spp., Anaplasma spp. e Bartonella spp. in domestics dogs and cats. The presence of these vectors, ticks and fleas, gives large-scale distribution of vector-borne diseases in the world, which in turn, have gained prominence in 2014 by the World Health Organization (WHO). The vector-borne diseases can be considered emerging or re-emerging and, in certain regions, its epidemiology is not yet defined. Therefore, this study aimed to identify vector-borne diseases agents by causing hemoparasitosis in domestic dogs and cats. Peripheral blood samples and ear tip were harvested from 110 animals, comprising 80 dogs and 30 cats. The animals were from the routine care and sterilization surgeries Veterinary Hospital of the University of Passo Fundo (HV-UPF), the city of Passo Fundo, Northwest, RS. The samples of dogs underwent blood smear by Giemsa and the Panotic staining, detection of anti-Babesia vogeli antibodies and anti-Ehrlichia canis by ELISA and PCR method for Babesia spp. (18S rRNA gene), Hepatozoon spp. (18S rRNA gene), Anaplasma spp. (16S rRNA) and Ehrlichia spp. (dsb gene). Blood smears revealed a total of 20% (22/110) of positive samples, and 63.63% (14/22) and 9.09% (2/22) having structures similar to morulae platelet and monocytes, respectively. Structures compatible with piroplasms were found in 27.27% (6/22). The other agents were not identified by these methods. Only animals infected with R. vitalii presented clinical and hematological alterations compatible with rangeliose, whose most common were anemia (100%), thrombocytopenia (66.7%), jaundice, external bleeding and anorexia (50%). The other positive animals identified with the other agents did not show clinical signs and/or hematological alterations compatible with infection caused by them. The detection of antibodies against B. vogeli showed seropositivity of 91% (73/80), while for B. vogeli and E. canis, only 8.75% (7/80). Nineteen (17.27%) of the 110 animals sampled were positive for some kind of hemoparasite in PCR. Eleven (10%) were positive for the 18S rRNA gene of Babesia spp., and after genetic sequencing identified the agent R. vitalii in 6 (5.5%) of dogs and B. vogeli in 3 dogs (2.72%) and 2 cats (1.81%). For the 18S rRNA gene Hepatozoon spp. only one dog was positive, as well as only one dogs (0.9%) were positive for 16S rRNA gene of Anaplasma spp. For nuoG gene Bartonella spp., 6 cats (20%) were positive. No sample was positive for dsb and 16S rRNA genes of Ehrlichia spp. In this study we report for the first time in the state of RS the molecular confirmation of B. vogeli in domestic dogs and cats. In addition, agents Hepatozoon spp., Anaplasma spp. and Bartonella spp. had not yet been described in the present study area. Furthermore, we suggest that R. vitalii is one of the most common vector-borne agents in RS